2017
DOI: 10.1007/s00395-017-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic cardiac ganglia and acetylcholine are important in the mechanism of ischaemic preconditioning

Abstract: This study aimed to investigate the role of the intrinsic cardiac nervous system in the mechanism of classical myocardial ischaemic preconditioning (IPC). Isolated perfused rat hearts were subjected to 35-min regional ischaemia and 60-min reperfusion. IPC was induced as three cycles of 5-min global ischaemia–reperfusion, and provided significant reduction in infarct size (IS/AAR = 14 ± 2% vs control IS/AAR = 48 ± 3%, p < 0.05). Treatment with the ganglionic antagonist, hexamethonium (50 μM), blocked IPC protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 68 publications
(90 reference statements)
4
41
3
2
Order By: Relevance
“…Consistently with our findings, previous studies have reported that DUSP1 downregulation was noted in fatty liver disease and cardiac ischemia reperfusion injury Pickard, Burke, Davidson, & Yellon, 2017;Zhou et al, 2018a) via modifying mitochondrial function, and that DUSP1 overexpression or pharmacological activation of DUSP1 retards or prevents the progression of nonalcoholic fatty liver F I G U R E 8 Downregulated DUSP1 induced by hyperglycemia amplified JNK pathway, promoting Mff phosphorylated activation. Increased Mff phosphorylation enhances fatal mitochondrial fission, leading to cellular oxidative stress, energy disorder, mitochondrial potential reduction, mPTP opening, cyt-c leakage into the cytoplasm, and the initiation of caspase-9-related glomerular mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently with our findings, previous studies have reported that DUSP1 downregulation was noted in fatty liver disease and cardiac ischemia reperfusion injury Pickard, Burke, Davidson, & Yellon, 2017;Zhou et al, 2018a) via modifying mitochondrial function, and that DUSP1 overexpression or pharmacological activation of DUSP1 retards or prevents the progression of nonalcoholic fatty liver F I G U R E 8 Downregulated DUSP1 induced by hyperglycemia amplified JNK pathway, promoting Mff phosphorylated activation. Increased Mff phosphorylation enhances fatal mitochondrial fission, leading to cellular oxidative stress, energy disorder, mitochondrial potential reduction, mPTP opening, cyt-c leakage into the cytoplasm, and the initiation of caspase-9-related glomerular mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, recent observations indicate that CypD can undergo covalent modifications, 51 and phosphorylated CypD is associated with an increased susceptibility to mPTP opening. 52 In our study, HR treatment had no effect on VDAC, ANT, and CypD expression ( Figure 5D-G); however, the phosphorylation of Ser31 by CypD was significantly increased in response to HR injury but was statistically decreased to normal levels by melatonin through abrogating Ripk3 activation ( Figure 5E and H). Therefore, these findings suggest that Ripk3 augments mPTP opening via upregulating CypD phosphorylation.…”
Section: Ripk3 Evokes Endothelial Necroptosis Via Inducing Cypd Phomentioning
confidence: 50%
“…Structurally, mPTP opening is facilitated by the binding of CypD to the inner mitochondrial membrane (IMM) . Notably, CypD binding to the IMM is enhanced by its phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
“…We then applied our technology to study the distribution of i.v.-injected magneto-EVs in an IRinjured mouse heart, which was induced through the ligation of the left anterior descending (LAD) coronary artery for 35 min, followed by reperfusion (37) (Figs. 5A,B).…”
Section: Biodistribution Of Ipsc-evs In Other Experimental Injury Modelsmentioning
confidence: 99%